The evaluation and implementation on the development of stimulation setting using CTML Model / Mohd Khairul Azlan Rahmat and Siti Zuraida Maaruf - Rahmat, Mohd Khairul Azlan; Maaruf, Siti Zuraida (UiTM Press, 2019)
This research aimed to identify the possibility and opportunity to implement the stimulation room courseware for drawing studies method in additional and substitute for the outdoor learning and indoor learning method in the teaching and learning of Drawing Studies subject in tertiary level of art education in Malaysia. Thus, this research is conducted in order to develop the stimulation room courseware for drawing studies that will be an optional teaching aid for the subject. This courseware and method will be an integrated use of ICT in the Visual Art Education field. This research was conducted by utilising the design development research (DDR) that consisted of three (3) phases. Phase 1: Needs Analysis, Phase 2: Design and Development and Phase 3: Implementation and Evaluation. However, for the purposed of this article, the researchers will only discuss Phase 3, that is the Implementation and Evaluation phase. The data was collected by the usability test form that has been given to three (3) experts in different fields; one (1) expert on videography, one (1) expert on interface design and one (1) expert on graphic design. The purpose of having this three (3) experts was to evaluate and provide feedbacks on the stimulation room courseware for drawing studies. Pre-test and post-test were carried out by eight (8) students of Art and Design that have undergone the subject of Drawing Studies using open-ended questionnaire. The feedbacks were then subjected to evaluation and assessment by two (2) experts in Drawing Studies. Based on the findings, the development of the stimulation method and the courseware is relevant and has possibilities for implementation in tertiary level art education in Malaysia.